Digital life on Instagram : new social communication of photography - Serafinelli, Elisa (Digital activism and society., 2018)
How does Instagram shape how we relate to each other online? Are users concerned about privacy when documenting their lives in fine detail? How does Instagram work as a marketing machine? Drawing on three years research with Instagram users, Elisa Serafinelli explores how Instagram is changing peoples visual experiences.Instagram is now by far the most popular online photo sharing platform, fuelled by the growth of smart mobile devices, and the management of an online persona is now part of millions of peoples everyday reality. This has not gone unnoticed among commercial actors, with the savviest of these exploiting the social dynamics of sharing that underlie the very logic of Instagram. This book addresses the issue of how mobile media and visual communication permeate peoples daily routines, how marketing influences practice, whether privacy and surveillance concerns are a reality, and how the platform shapes social relationships and identity formation. In its conclusion, the book advances the innovative concept of new mobile visualities to describe the social communication of photography and its huge expansion. 'Digital Life on Instagram' is an online ethnography fit for the modern age of social media.